The endoscopic and clinical characteristics of patients with erosive reflux disease diagnosed in gastroscopy unit of a regional hospital. Issue 2 (2012) - Tunç, Nurettin; Şıkgenç, Mehmet Mahfuz; Yakut, Mustafa
No abstract available